MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN PROSPERITY BUSINESS ACTORS DURING THE COVID-19 PANDEMIC IN THE VILLAGE ANAIWOI - Amin, Muhtar; Saleh, Ramlah; Masitah, Masitah; Ufayani, Nia (IJBLE Scientific Publications Community Inc., 2023)
Micro, Small, and Medium Enterprise (MSMEs) are self-sufficient business units, which is done by individuals or an effort in all economic sector. The role of MSMEs in the Indonesian economy is shown by their role as perpetrator business biggest, as well contribution to absorption power work, formation of Product Domestic Gross (GDP), exports and fixed capital creation/investment. In this research, the role of MSMEs can be seen from 4 variables, namely health, education, pattern consumption and social other. The purpose of this research is to find out how the role of Micro, Small, and Medium Enterprises is in prosperity perpetrator business during the Covid-19 pandemic in the Village Anaiwoi. The research was conducted from May to June 2022. This research uses an approach qualitative and quantitative methods. The data analysis used is a rating scale analysis. The results of the study show that the value of 1,476 is included in the interval category